Cardenolide and pregnatriene compounds from the roots of Nerium oleander - Mishra V.K.; Rathour B.K.; Mishra S.K.; Sagar R. (My University, 2025)
Cardenolide and pregnatriene compounds were isolated from the chloroform fraction of the 95% aqueous ethanolic extract of dried roots of Nerium oleander. The stereochemical structure of the cardenolide and pregnatriene compounds was determined to be 3β-O-(D-diginosyl)-14β-hydroxy card-20(22)-enolide and 12β-hydroxy pregna-4,6,16-triene-3,20-dione using spectroscopic methods including IR, HRMS and NMR spectroscopy. © 2020 Informa UK Limited, trading as Taylor & Francis Group.